Analysis of landrace cultivation in Europe: A means to support in situ conservation of crop diversity. (March 2022) - Raggi, Lorenzo; Pacicco, Luca C.; Caproni, Leonardo; Álvarez-Muñiz, Clara; Annamaa, Külli; Barata, Ana M.; Batir-Rusu, Diana; Díez, María J.; Heinonen, Maarit; Holubec, Vojtěch; Kell, Shelagh; Kutnjak, Hrvoje; et al.
Abstract: During the last century, the progressive substitution of landraces with modern, high yielding varieties, led to a dramatic reduction of in situ conserved crop diversity in Europe. Nowadays there is limited and scattered information on where landraces are cultivated. To fill this gap and lay the groundwork for a regional landrace in situ conservation strategy, information on more than 19, 335 geo-referenced landrace cultivation sites were collated from 14 European countries. According to collected data, landraces of 141 herbaceous and 48 tree species are cultivated across Europe: Italy (107 species), Greece (93), Portugal (45) and Spain (44) hold the highest numbers. Common bean, onion, tomato, potato and apple are the species of main interest in the covered countries. As from collected data, about 19.8% of landrace cultivation sites are in protected areas of the Natura 2000 network. We also got evidence that 16.7% and 19.3% of conservation varieties of agricultural species and vegetables are currently cultivated, respectively. Results of the GIS analysis allowed the identification of 1261 cells (25 km × 25 km) including all the cultivation sites, distributed across all European biogeographical regions. Data of this study constitute the largest ever produced database of in situ -maintained landraces and the first attempt to create an inventory for the entire Europe. The availability of such resource will serve for better planning of actions and development of policies to protect landraces and foster their use. Highlights: 19, 335 geo-referenced landrace cultivation sites recorded in Europe. 189 crop species cultivated as landraces across 14 European countries. 19.8% of landrace cultivation sites in Natura 2000 protected areas Landrace cultivation sites in all European biogeographical regions